A penetrating orbitocranial stab wound. Issue 2 (February 1986) - MacEwen, C J; Fullarton, G
Abstract : An unusual case of intracranial penetration of a bread knife through the orbit is described. Despite the proximity of the blade to the internal carotids, the optic nerves and chiasm, and the pituitary the patient survived with only a minimal field defect affecting the eye opposite to the entry site; otherwise no neurological or endocrine deficit was evident.